Engagement Education: A Model of Community-Youth Engagement in Rural Appalachia - Sharon Casapulla; Michael E. Hess (The University of Alabama, 2022)
In this paper we present a framework for teaching and learning that applies Boyer's definition of engaged scholarship to K-12 education by engaging students, teachers, and community members as partners in learning in a reciprocal relationship that strengthens schools and communities. We call this model, which emerged during a community-based project with rural high school students, engagement education. In this model, teaching and learning are place-focused, project-based, asset-driven, and democratically oriented. We present the framework that lies at the intersection of the four approaches mentioned above by first describing each approach individually. We discuss each component of the engagement education framework within the context of the school and community-based project from which it emerged. We share the findings from a qualitative analysis of the students' reflections at the completion of the project. Finally, we discuss implications for engaged scholars working with rural communities and schools.